An Eco-Systematic View of Cross-Sector Fintech: The Case of Alibaba and Tencent - Zhang-Zhang, Yingying; Rohlfer, Sylvia; Rajasekera, Jay (Sustainability, 2020)
This paper explores the most recent Fintech (financial technology) phenomenon from an ecosystem perspective. Differentiated from the earlier Fintech evolution led by traditional financial institutions, “cross-sector” Fintech that operates at the intersection of financial services and information technology disrupts existing business models of banks while creating novel ecosystem dynamics. This study explores the Fintech ecosystem composition to understand better business model innovation based on underlying ecosystem dynamics while focusing on the specific role of cross-sector actors. These actors have escaped scrutiny despite being mature and experienced and having strong resource bases. Adopting a comparative case study method by considering the China-based Alibaba Group and Tencent, the study’s findings indicate that novel business model developments based on strong technological expertise and scale-based resources by cross-sector Fintech render a functional perspective on fast-developing Fintech industry less practical. Apart from cross-sector Fintech, investors constitute a new dimension in the conceptualization of the Fintech ecosystem. Overall, the interconnectedness of the cross-sector Fintech beyond the Fintech sectors drives the fuzzy boundaries between ecosystems, established business models, terminology definitions, ecosystem actors’ roles and relationships, which appear to become more heterogeneous and changeable over time. The study contributes to the scant literature on Fintech ecosystems and their sustainable development.